2013
DOI: 10.1590/s1983-80422013000300014
|View full text |Cite
|
Sign up to set email alerts
|

Criminalização do aborto no Brasil e implicações à saúde pública

Abstract: ResumoDiscussões inerentes ao aborto no Brasil suscitam reflexões relacionadas a aspectos sociais, culturais, morais, legais, econômicos, bioéticos, religiosos e ideológicos. O aborto emergiu como questão de saúde pública, em razão do elevado índice de morbimortalidade materna. O estudo objetiva discutir a criminalização do aborto no Brasil e implicações à saúde pública. Trata-se de revisão crítica, realizada nas bases de dados Lilacs e SciELO. Evidenciou-se que o déficit na qualidade da assistência prestada, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
16

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 13 publications
1
9
0
16
Order By: Relevance
“…O aborto é um tema polêmico e enfrenta barreiras religiosas, políticas e de conflitos éticos e provavelmente a implantação de atendimento adequado esbarra nestas questões 21,22 .…”
Section: Discussionunclassified
“…O aborto é um tema polêmico e enfrenta barreiras religiosas, políticas e de conflitos éticos e provavelmente a implantação de atendimento adequado esbarra nestas questões 21,22 .…”
Section: Discussionunclassified
“…I took the medicine home and throw it away ... he showed me various medicines, which several young girls would do and abort, and I said to him like that: if we do it and it's not aborting, it's born sick, and 'there' we will get more complicated ... because the two of us 'had' to be together at all costs because if you are good health is already very difficult, imagine sick. (IRIS,19)  Reactions of friends and society in the face of teenage pregnancy It was observed that the reactions of the friends before the pregnancy of the young woman were mostly of happiness and joy, as it is observed in the statements of the following deponents:…”
Section:  Family Reactions To Teenage Pregnancymentioning
confidence: 97%
“…My colleagues reacted well, they thought it was cool for me to have the child. (BEGÔNIA,19) My friends liked it, no one moved away from me no, they got closer. (HORTÊNCIA,19) Thank God my friends helped me a lot to accept what is happening to me, they stayed by my side and they felt happy too.…”
Section:  Family Reactions To Teenage Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…It's well known that abortion, a serious public health problem, is present in the Brazilian society, and it is a topic that generates much discussion, both for the defence of its legalisation as well as for the continuation, partial or unrestricted, of its prohibition 1 . Despite the fact that the academic background of health professionals includes various approaches to the subject, the influences of ethical, moral, socio-economic, political, cultural and religious issues end up bringing difficulties to the debate.…”
mentioning
confidence: 99%